2007
DOI: 10.1186/1472-6963-7-193
|View full text |Cite
|
Sign up to set email alerts
|

The effect of priority setting decisions for new cancer drugs on medical oncologists' practice in Ontario: a qualitative study

Abstract: Background: Health care policies, including drug-funding policies, influence physician practice. Funding policies are especially important in the area of cancer care since cancer is a leading cause of death that is responsible for a significant level of health care expenditures. Recognizing the rising cost of cancer therapies, Cancer Care Ontario (CCO) established a funding process to provide access to new, effective agents through a "New Drug Funding Program" (NDFP). The purpose of this study is to describe o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 13 publications
0
26
0
1
Order By: Relevance
“…Physicians have been reported to discuss drug costs with patients [14,15,21,44]. The willingness to do so is dependent on the level of reimbursement of medicines within the health care system.…”
Section: Patient-physician Relationshipmentioning
confidence: 99%
See 2 more Smart Citations
“…Physicians have been reported to discuss drug costs with patients [14,15,21,44]. The willingness to do so is dependent on the level of reimbursement of medicines within the health care system.…”
Section: Patient-physician Relationshipmentioning
confidence: 99%
“…However, some report the need for autonomy in their treatment decisions and are unwilling to accept restrictions imposed by governments and health authorities and will resist or find ways to overcome these restrictions [15]. Physicians -in their role as patient advocates -would like politicians to take responsibility for funding decisions [28,43].…”
Section: Health Policymentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of catastrophic health expenditures was significantly higher among patients who underwent chemotherapy. 16 Berry et al, 20 in their qualitative study in Canada, found that oncologists talk more with patients about access to drugs being limited due to funding decisions. The American Society of Clinical Oncology (ASCO) considers physician-patient communication about the cost of care to be an important component of high-quality care.…”
Section: Discussionmentioning
confidence: 99%
“…Medical oncologists can have an important role in controlling the cost of cancer treatments. 20 They are the main decisionmakers in the treatment process and decide what medications a patient should use. 21 Although oncologists want their patients to receive the treatment that provides the greatest benefit, however, they must also consider the costs of treatment, because high-cost treatment may impose a financial burden on patients and society and reduce their welfare.…”
Section: Key Messagesmentioning
confidence: 99%